Plants, Land, and Indigenous Philosophy: Poetics of Ecosemiosphere in Rituals of Tharu - Dangaura, Mohan (BMC Research Journal, 2026)
This article argues that Tharu rituals reflect an ecocritical consciousness embedded within their songs and performances. Rooted in plants, land, and indigenous philosophy, Tharu rituals demonstrate an ecosemiospherial relation between people and nature. Their rituals signify beyond simple cultural expressions, serving as vital parts of the environmental humanities. These practices emphasize the often-overlooked relationship between sustainability and daily life by illustrating how traditional customs support ecological balance. Viewing Tharu rituals through the lenses of ecology and semiotics provides valuable insights into how communities function as environmental entities. In particular, the community’s Lwangi Puja ritual, currently threatened by rising river pollution, highlights the urgent need to preserve such rituals, which have historically promoted community well-being. These rituals exemplify ecological identity formation through myth, culture, and environment. Using the theories of Charles Sanders Peirce and Jakob von Uexküll, this article explores the relations between physical and cultural meanings across the material and spiritual aspects of Tharu worldview. The Tharu people express their understanding of nature through myths, stories, and customs woven into their relationship with the land. By analyzing Tharu folk performances through ecological and semiotic perspectives, this article demonstrates how indigenous communities function as dynamic environmental entities and contribute valuable insights to contemporary ecological discourse